WACANA MAGIS DALAM KORAN POSMO edisi ke 748, 9 Oktober 2013 - Reva Efendi Putra Utama (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study took the object of the 748th edition of the Posmo newspaper, this study focused on analyzing the elements of magical realism contained in the object. This is done with the hope that the research results can add to the scientific treasures in the field of language and literature. The scope of this study intends to reveal the elements of magical realism contained in Posmo newspaper edition 748. The research method in this journal is descriptive qualitative, data collection techniques taken using literature study with several stages, namely, reading, recording, coding and so on. analyzed. The data analysis technique used in processing the object is a qualitative descriptive data analysis technique, text interpretation. This research produces data in the form of elements of magical realism in the discourse narratives contained in the object in the form of the 748th edition of the Posmo newspaper.